Drought prediction in inland valleys rice-based production systems in the Sudan-Sahel Zone - CGIAR Research Program on Rice (2019)
We identified the best covariates for drought occurrence in inland valleys rice-based production systems. The overall prediction accuracy of the approach was 98%. Inland valleys with an annual standardized precipitation evapotranspiration index lower than -0.02 and duration of groundwater shorter than 15 weeks were demonstrably more prone to drought.